2015
DOI: 10.1016/j.ijpsycho.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of explicit knowledge and predictability on auditory distraction and target performance

Abstract: This study tested effects of task requirements and knowledge on auditory distraction effects. This was done by comparing the response to a pitch change (an irrelevant, distracting tone feature) that occurred predictably in a tone sequence (every 5th tone) under different task conditions. The same regular sound sequence was presented with task conditions varying in what information the participant was given about the predictability of the pitch change, and when this information was relevant for the task to be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
5
12
0
Order By: Relevance
“…This suggestion would be in line with a variety of studies demonstrating participants' ability to implicitly improve performance due to statistical (Hannula & Greene, 2012;Henke, 2010;Turk-Browne et al, 2009, 2010 and perceptual learning (Seitz, 2017;Seitz & Watanabe, 2009); in addition, studies on temporal attention showed that target detection in attentional blink paradigms and block-wise manipulations of TEs can be based on implicit learning (Ball et al, 2018a(Ball et al, , 2018bShen & Alain, 2012;Visser, Ohan, & Enns, 2015). Our results are also in line with results from various other paradigmssuch as contextual cueing, perceptual priming, motor sequence learning, and timing tasksshowing no improvement in behavioral effects when comparing influences of implicit and explicit knowledge on performance within the same paradigm (Chun & Jiang, 2003;Francken, Gaal, & de Lange, 2011;Geyer, Baumgartner, Müller, & Pollmann, 2012;Max, Widmann, Schröger, & Sussman, 2015;Preston & Gabrieli, 2008;Sanchez & Reber, 2013;Van den Bussche et al, 2013;Westerberg, Miller, Reber, Cohen, & Paller, 2011).…”
Section: Comparison With the Previous Studysupporting
confidence: 89%
See 1 more Smart Citation
“…This suggestion would be in line with a variety of studies demonstrating participants' ability to implicitly improve performance due to statistical (Hannula & Greene, 2012;Henke, 2010;Turk-Browne et al, 2009, 2010 and perceptual learning (Seitz, 2017;Seitz & Watanabe, 2009); in addition, studies on temporal attention showed that target detection in attentional blink paradigms and block-wise manipulations of TEs can be based on implicit learning (Ball et al, 2018a(Ball et al, , 2018bShen & Alain, 2012;Visser, Ohan, & Enns, 2015). Our results are also in line with results from various other paradigmssuch as contextual cueing, perceptual priming, motor sequence learning, and timing tasksshowing no improvement in behavioral effects when comparing influences of implicit and explicit knowledge on performance within the same paradigm (Chun & Jiang, 2003;Francken, Gaal, & de Lange, 2011;Geyer, Baumgartner, Müller, & Pollmann, 2012;Max, Widmann, Schröger, & Sussman, 2015;Preston & Gabrieli, 2008;Sanchez & Reber, 2013;Van den Bussche et al, 2013;Westerberg, Miller, Reber, Cohen, & Paller, 2011).…”
Section: Comparison With the Previous Studysupporting
confidence: 89%
“…The results presented here suggest that although the average RT effects appeared to be qualitatively similar, they are potentially based on different mechanisms as indicated by the DDM. Thus, similar appearing average behavioral readouts across groups might be driven by different neural processes (see, e.g., Max et al, 2015;Preston & Gabrieli, 2008). Putting the DDM results in context with our hypothesis, they suggest that the temporal expectation effects were driven not only by bottom-up but also top-down effects.…”
Section: Bottom-up Top-down or Bias?supporting
confidence: 56%
“…And most within-study comparisons of explicitly versus implicitly driven behaviour report the absence of modulating effects due to explicit knowledge. For instance, Max et al ( 2015 ) investigated the impact of distracting sounds (deviant pitch) within a sequence of standard sounds on auditory duration judgments. The authors found no evidence that instructions (explicit vs. no information) altered behavioural performance related to the distraction effect, though they observed changes in the EEG signals (i.e., a lower P3a amplitude when distractors were expected due to instructions).…”
Section: Discussionmentioning
confidence: 99%
“…However, a difference in behaviour or neural activation patterns – when based on different experimental paradigms or studies without assessment of participants’ explicit knowledge – would be insufficient to conclude that explicit knowledge truly affects e. g. performance and learning patterns (Ball et al, 2019); and most within-study comparisons of explicitly- vs. implicitly-driven behaviour report the absence of modulating effects due to explicit knowledge. For instance, Max and colleagues (2015) investigated the impact of distracting sounds (deviant pitch) within a sequence of standard sounds on auditory duration judgments. The authors found no evidence that instructions (explicit vs. no-information) altered behavioural performance related to the distraction effect, though they observed changes in the EEG signals (i.e.…”
Section: Discussionmentioning
confidence: 99%